Women of Jordan : Islam, labor & the law - Sonbol, Amira El Azhary (Gender, culture, and politics in the Middle East., 2003)
Sonbol (Islamic history, society, and law, Georgetown U.) presents 12 chapters discussing the spectrum of legal and work-related obstacles faced by women, both in the past and in the present, in Jordan. Chapters include women's role in the world of work in Jordan historically and in contemporary times; laws of guardianship and the construction of gender; marriage, obedience, and work; honor crimes; and work and the modern Jordanian woman. Annotation (c)2003 Book News, Inc., Portland, OR (booknews.com).